Pengaruh Gaya Kepemimpinan, Disiplin Kerja, Motivasi Kerja dan Kepuasan Kerja Terhadap Produktivitas Karyawan Restoran Malang (Studi Pada Ayam Geprek Sa’i) - Mandasari, Adinda Putri; Arifin, Rois; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study examines leadership style, work discipline, work motivation and job satisfaction on the productivity of employees of a poor restaurant (ayam geprek sa'i). Using a quantitative approach with a survey method, this study involved 75 respondents selected by saturated sampling technique Data were collected through questionnaires employing a saturated sampling technique and analyzed using multiple linear regression. The results demonstrated that, together, the four variables had a significant impact on employee productivity. However, partially, only work discipline and work motivation have a significant effect, while social leadership style and job satisfaction have a negative effect. These findings suggest that it is important for restaurant management to pay attention to factors Factors such as leadership style, work discipline, motivation, and job satisfaction are essential for enhancing employee productivity in the highly competitive culinary sector. Keywords: Leadership Style, Work Discipline, Work Motivation, Job Satisfaction, Employee Productivity, Ayam Geprek Sa'i